Neurálna aktivita v čuchovom systéme indukovaná netypickým čuchovým stimulom - Závodská, Monika; Saganová, Kamila; Martončíková, Marcela; Angelidis, Andreas; Arnoulová, Petra; Račeková, Enikö (Psychiatrie (Praha, Print), 2017)
x